An Assessment of Earthworm as Bioindicator for Heavy Metal Contamination in Pasture Land Adjacent To A Highway - Wee, Pou Lis (2008)
The present study showed that Perionyx excavatus, Pontoscolex corethrurus, Amynthas gracilis, Dichogaster bolaui and Eudrilus euginiae could be found in UPM pasture land, with the horizontal burrower, P. corethrurus as the most common species. Metal concentrations in soil at different distances were analyzed to determine safe distance and traffic as the main source of roadside heavy metal pollution. Even though most of the traffic pollution studies were based on total heavy metal concentrations in soil, but the present studies on distribution and speciation of heavy metals in soil could provide clearer picture on the degree of heavy metals pollution, their origin, metal bioavailability and actual environmental impact on metal bioavailability. The bioavailable metal in UPM pasture soil was compared to the total metal content and the percentages of bioavailable metal for Zn, Cu, Cd and Pb in the soil were 45.91%, 21.47%, 10.04% and 40.74% respectively. The level of metals in the soil and grass were still below the critical level set by many other countries. A good biomonitor for heavy metals traffic pollution should have high Bioaccumulation Factor (BAF) value and correlate positively with the traffic volume. BAFs order for the metals in grass, B. decumbens was Zn>Cu>Pb>Cd. The rhizome of B. decumbens has the highest BAF for Zn, root has the highest BAF for Cu and Pb. For the earthworm, P. corethrurus, the BAFs order for metals was Cd>Zn>Cu>Pb. The bioavailable Cd and Pb in the soil were positively correlated with traffic volume. Lead in earthworms, Zn and Cu in B. decumbens stems and Zn in the rhizomes also increased with traffic volume. The present study suggested that Pb in earthworm P. corethrurus and Zn in the rhizome of B. decumbens could be used as an integrated assessment to monitor heavy metal traffic pollution as they have high BAF and correlated positively with traffic volume.